2019
DOI: 10.1103/physrevmaterials.3.084604
|View full text |Cite
|
Sign up to set email alerts
|

p -type codoping effect in (Ga,Mn)As: Mn lattice location versus magnetic properties

Abstract: In the present work, we perform a systematic investigation on p-type co-doping in (Ga,Mn)As. Through gradually increasing Zn doping concentration, the hole concentration increases, which should theoretically lead to an increase of the Curie temperature (TC) according to the p-d Zener model. Unexpectedly, although the film keeps its epitaxial structure, both TC and the magnetization decrease. The samples present a phase transition from ferromagnetism to paramagnetism upon increasing hole concentration. In the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Additionally, the thermo-remanent magnetization at 5 K decreases from 23.0, via 20.3, finally to 14.1 emu/cm 3 . Actually, the suppression of magnetization and Curie temperature induced by Al doping has been observed in a series of (Ga,Mn)As samples [ 13 ]; in a study by [ 3 ], there were two different mechanisms proposed: (i) part of Mn atoms are driven into the interstitial sites; and (ii) the localization of carriers is enhanced by Al alloying due to stronger p-d exchange coupling However, in the low Al concentration doped region (<20%), the first function worked dominantly, and a similar phenomenon appeared in Zn-doped (Ga,Mn)As according to our previous research [ 14 ]. This is the most probable explanation for the Al-doped (In,Mn)As case, since, for the highest Al concentration doped sample, it is observed that in addition to the reduction in Curie temperature, the M–T curve deviates from the mean-field approximation, and such a phenomenon is in good agreement with a decrease in substitutional Mn concentration [ 24 ].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, the thermo-remanent magnetization at 5 K decreases from 23.0, via 20.3, finally to 14.1 emu/cm 3 . Actually, the suppression of magnetization and Curie temperature induced by Al doping has been observed in a series of (Ga,Mn)As samples [ 13 ]; in a study by [ 3 ], there were two different mechanisms proposed: (i) part of Mn atoms are driven into the interstitial sites; and (ii) the localization of carriers is enhanced by Al alloying due to stronger p-d exchange coupling However, in the low Al concentration doped region (<20%), the first function worked dominantly, and a similar phenomenon appeared in Zn-doped (Ga,Mn)As according to our previous research [ 14 ]. This is the most probable explanation for the Al-doped (In,Mn)As case, since, for the highest Al concentration doped sample, it is observed that in addition to the reduction in Curie temperature, the M–T curve deviates from the mean-field approximation, and such a phenomenon is in good agreement with a decrease in substitutional Mn concentration [ 24 ].…”
Section: Resultsmentioning
confidence: 86%
“…Even for the most canonical DFS (Ga,Mn)As, mostly low-temperature molecular beam epitaxy (LT-MBE) has been employed for its epitaxial film preparation [ 4 , 7 , 8 ], which significantly prohibited the development of DFSs. Moreover, such an obstacle threatens the most conventional technique of semiconductor modification, i.e., co-doping which is productive to present new physics [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, ion implantation followed by the pulsed laser melting method provides an alternative solution to this problem due to its second non-equilibrium grown essence, and therefore, it has been used in several hyper-doping cases in which some are even impossible to approach by LT-MBE [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For electrical gating, the samples have to be as thin as several nano-meters due to the extremely high carrier concentrations [2,4,6]. In (Ga,Mn)As co-doped with Be/Zn acceptors, Mn ions are kicked out from substitutional sites to interstitial sites [10,14]. Note that interstitial Mn ions are double donors in GaAs and can develop anti-ferromagnetic coupling [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…After hydrogenation, a postannealing at low temperature has to be applied to remove the Mn-H complexes and recover the hole concentration over a wide range by varying the annealing time [14]. In (Ga,Mn)As co-doped with Be/Zn acceptors, Mn ions are kicked out from substitutional sites to interstitial sites [11,17]. Note that interstitial Mn ions are double donors in GaAs and can develop anti-ferromagnetic coupling [18,19].…”
Section: Introductionmentioning
confidence: 99%